Investigating Anti-mutagenic Activities of Lantana camara L. (Verbenaceae) Applying Salmonella typhimurium and the Ames Test - Zahra Zare (Zabol University of Medical sciences, 2020)
Introduction: Genetic mutations have a significant role in causing cancers, and plants are effective on cancer recovery by producing metabolites. In this regard, the present study aimed to evaluate the Lantana camera anti-mutation effects applying Salmonella typhimurium in the Ames test. Methods: To this end, the plant was prepared from the Iran National Botanical Garden in 2018 (Tehran, Iran), and the methanolic extracts of its leaves and flowers were obtained by the percolation method. Then, anti-mutagenic activities were studied by the Ames method and the assessment of the rate of reverse mutations in mutant Salmonella typhimurium. Mutant strains cannot grow on minimal mineral media thus only those bacteria that have acquired a wild genotype after reverse mutation in the presence of the mutagen are able to grow on this medium. The plant extract, along with a mutagen substance was used to evaluate its anti-mutagenic effects by counting grown colonies and calculating the mean mutation inhibitory index according to the "Ong" formula. Finally, anti-mutagenic activities were retested by adding the sterile extract of the mouse liver (S9), and the data were analyzed by SPSS statistical software, version 22.Results: In general, the results showed that the mean number of grown colonies decreased significantly despite the plant material in comparison with the standard. According to the "Ong" formula, the percentage of inhibition was [1-T/M]×100. Based on the results, T grew a number of colonies on each petri dish despite the mutagen and extract, and M grew a number of colonies in positive control plates. Eventually, mutation inhibition percentages in leaf extracts were significantly higher than those of flower extracts, which were 75.59 ± 0.73 (+S9) and 84.79 ± 0.17 (-S9), as well as 49.57 ± 0.55 (+S9) and 62.32 ± 0.23 (-S9), respectively (P < 0.05). Conclusion: In general, the leaves and flowers of L. camara demonstrated anti-mutagenic activities with higher activities in the leaves compared to flowers.